Practicing the Alternative. The Impact of the Crisis in Latin America through a Gender Perspective Analysis - Perini, Lorenza (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
This paper intends to analyze the impacts of the 2008 economic crisis with a gender perspective, focusing on Latin America (in this case considered as a region, although the single countries have been affected in different ways by the crisis, due to the particular economic situation of each). The main target of the research is to evaluate how austerity perpetuates gender inequality in contexts like labor market and migration, and to advocate for sustained investment in gender equality. The idea is to demonstrate, through some practical examples, why there is a need to give attention to women’s movements, invest on women and girls’ education, knowledge, culture capabilities, competences and skills, especially during economic crisis, in order to transform the existing market and the existing models of production in society.The paper wants to underline the correlation between the general and classic indicators of the economic crisis (work / development / migration / welfare state) and some of the possible “gender variables”. The analysis of this complex scenario is framed through a feminist economic approach, in order to broaden the idea of what economy is, by looking at the consequences of the economic model in times of crisis in people’s lives, bringing into light that women’s economic and social contributions are invisible under the hegemonic patriarchal model we live in.Finally, some consideration are drawn on the fact that the development of communitarian economies and cooperative systems, very relevant in Latin America, is part of an indigenous, peasant tradition and it can be interpreted as an approximation of an alternative feminist economic model, in order to compensate the lack of welfare with the women’s cooperation on reproduction. In this sense, many examples of cooperatives run by women are presented in the last part of the research. This, however, should not be seen as a justification for things not to change, but an incentive to invest in women, their education and their  opportunities to participate in the economy since considering care and reproductive work as the core of the commons, as Federici has stated, it is not a matter of identity but a matter of challenging the hierarchy of power from the very basis.This paper intends to analyze the impacts of the 2008 economic crisis with a gender perspective, focusing on Latin America (in this case considered as a region, although the single countries have been affected in different ways by the crisis, due to the particular economic situation of each). The main target of the research is to evaluate how austerity perpetuates gender inequality in contexts like labor market and migration, and to advocate for sustained investment in gender equality. The idea is to demonstrate, through some practical examples, why there is a need to give attention to women’s movements, invest on women and girls’ education, knowledge, culture capabilities, competences and skills, especially during economic crisis, in order to transform the existing market and the existing models of production in society.The paper wants to underline the correlation between the general and classic indicators of the economic crisis (work / development / migration / welfare state) and some of the possible “gender variables”. The analysis of this complex scenario is framed through a feminist economic approach, in order to broaden the idea of what economy is, by looking at the consequences of the economic model in times of crisis in people’s lives, bringing into light that women’s economic and social contributions are invisible under the hegemonic patriarchal model we live in.Finally, some consideration are drawn on the fact that the development of communitarian economies and cooperative systems, very relevant in Latin America, is part of an indigenous, peasant tradition and it can be interpreted as an approximation of an alternative feminist economic model, in order to compensate the lack of welfare with the women’s cooperation on reproduction. In this sense, many examples of cooperatives run by women are presented in the last part of the research. This, however, should not be seen as a justification for things not to change, but an incentive to invest in women, their education and their  opportunities to participate in the economy since considering care and reproductive work as the core of the commons, as Federici has stated, it is not a matter of identity but a matter of challenging the hierarchy of power from the very basis.
Keywords: economic crisis; gender perspective